Clinical Utilization of Multimodality Imaging for Myocarditis and Cardiac Sarcoidosis. (17th January 2023) - Chareonthaitawee, Panithaya; Gutberlet, Matthias
Abstract : Myocarditis is defined as inflammation of the myocardium according to clinical, histological, biochemical, immunohistochemical, or imaging findings. Inflammation can be categorized histologically by cell type or pattern, and many causes have been implicated, including infectious, most commonly viral, systemic autoimmune diseases, vaccine-associated processes, environmental factors, toxins, and hypersensitivity to drugs. Sarcoid myocarditis is increasingly recognized as an important cause of cardiomyopathy and has important diagnostic, prognostic, and therapeutic implications in patients with systemic sarcoidosis. The clinical presentation of myocarditis may include an asymptomatic, subacute, acute, fulminant, or chronic course and may have focal or diffuse involvement of the myocardium depending on the cause and time point of the disease. For most causes of myocarditis except sarcoidosis, myocardial biopsy is the gold standard but is limited due to risk, cost, availability, and variable sensitivity. Diagnostic criteria have been established for both myocarditis and cardiac sarcoidosis and include clinical and imaging findings particularly the use of cardiac magnetic resonance and positron emission tomography. Beyond diagnosis, imaging findings may also provide prognostic value. This case-based review focuses on the current state of multimodality imaging for the diagnosis and management of myocarditis and cardiac sarcoidosis, highlighting multimodality imaging approaches with practical clinical vignettes, with a discussion of knowledge gaps and future directions.